2004
DOI: 10.1089/thy.2004.14.1097
|View full text |Cite
|
Sign up to set email alerts
|

Graves' Disease after Interleukin-2 Therapy in a Patient with Human Immunodeficiency Virus Infection

Abstract: Interleukin-2 (IL-2) is a cytokine that regulates the proliferation and differentiation of lymphocytes, and is currently used clinically in the treatment of assorted malignancies. Additionally, IL-2 is being actively investigated in clinical trials for treatment of human immunodeficiency virus (HIV) infection. Patients treated with IL-2 are susceptible to autoimmune thyroid disease (AITD), presenting as thyroiditis, which leads to either thyrotoxicosis or hypothyroidism, if not correctly and promptly identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…After this period, naive CD4 T-cell numbers slowly improve as a result of repopulation and new thymic production. Graves' disease may also be associated with Interferon Alpha (IFN α ) used to treat hepatitis C and Interleukin 2 (IL-2) therapy in the setting of HIV [3, 9]. Earlier studies found that TPO antibodies and TSH receptor antibodies appeared after CD4 T cells had dramatically increased on HAART, whereas they were repeatedly absent prior to HAART [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After this period, naive CD4 T-cell numbers slowly improve as a result of repopulation and new thymic production. Graves' disease may also be associated with Interferon Alpha (IFN α ) used to treat hepatitis C and Interleukin 2 (IL-2) therapy in the setting of HIV [3, 9]. Earlier studies found that TPO antibodies and TSH receptor antibodies appeared after CD4 T cells had dramatically increased on HAART, whereas they were repeatedly absent prior to HAART [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, a minority of patients might experience a paradoxical clinical decline as a result of immune restitution [2]. This phenomenon occurs by virtue of restoration of the capacity to mount an inflammatory response against both infectious and noninfectious antigens [3], hence the term immune reconstitution inflammatory syndrome (IRIS). IRIS occurs most commonly as a result of reactivation of infections such as Mycobacterium avium complex, Mycobacterium tuberculosis , Cryptococcus neoformans, or cytomegalovirus and tends to occur between a few weeks and several months after initiating HAART, corresponding with CD4 positive memory cell repopulation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest the CD4 cells increase in a biphasic pattern after HAART initiation, with initial redistribution of memory CD4 cells from lymphoid tissue followed, months later, by expansion of naive CD4 cells [44]. Consistent with this explanation is the observation of transient Graves' disease among HIV-infected patients with naive CD4 cell expansion driven by IL-2 treatment [45]. However, delineating the timing and pattern of cell types in CD4 cell reconstitution remains an area of ongoing research [46].…”
Section: Increased Thyroid Functionmentioning
confidence: 95%
“…Human interleukin-2 (hIL2) is a natural polypeptide hormone, which has a key role in activating a network of immune responses within the body (Kaplan et al, 1992;Yamaguchi et al, 2003). The critical role of hIL2 has led to clinical trials for the treatment of several deadly diseases, including cancer (Bubenik, 2004;Eklund and Kuzel, 2004;McDermott and Atkins, 2004;Porta, 2006;Stroncek et al, 2005) and AIDS (Jacobson et al, 1996;Jimenez et al, 2004;Martin et al, 2005;Smith et al, 1999). The clinical efficacy of hIL2 makes it an appropriate therapeutic protein for development of usage in biohybrid organs.…”
Section: Introductionmentioning
confidence: 99%